2008
DOI: 10.4103/0378-6323.41374
|View full text |Cite
|
Sign up to set email alerts
|

Goldenhar syndrome with unusual features

Abstract: We report here the case of a 17 year-old girl with the classic signs of Goldenhar syndrome in the form of multiple accessory tragi, bilateral ocular dermoids, mandibular hypoplasia (micrognathia) and cervical lordosis. She also had a high arched palate, gingival hypertrophy and malaligned teeth, features which are as yet unreported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 0 publications
0
32
0
5
Order By: Relevance
“…The exact aetiology is not known. However, it is possible that the abnormal embryonic vascular supply, distrupted mesodermal migration or some other factor leads to defective formation of the branchial arches and vertebral systems [3]. Kallen et al, reported that most of the cases were sporadic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact aetiology is not known. However, it is possible that the abnormal embryonic vascular supply, distrupted mesodermal migration or some other factor leads to defective formation of the branchial arches and vertebral systems [3]. Kallen et al, reported that most of the cases were sporadic.…”
Section: Discussionmentioning
confidence: 99%
“…Social workers can provide support and guidance to the children and their families, such as accessing community resources, making decisions about surgeries and adjusting for the facial asymmetry. Prognosis of this disease is good in otherwise uncomplicated cases without any systemic associations [3].…”
Section: Etiologymentioning
confidence: 95%
See 2 more Smart Citations
“…It is more common among males, with male:female ratio of 3:2. 1 It involves abnormalities in the first and second branchial arches. The etiology of the syndrome is heterogeneous.…”
Section: Introductionmentioning
confidence: 99%